Influence of surface structure and tube material on the condensation heat transfer coefficient of n-butane on horizontal single tubes and in tube bundles - Kühl, Julius; Palm, Franz; Dietl, Jochen; El Hajal, Jean; Gotterbarm, Achim; Rausch, Michael Heinrich; Klein, Tobias; Fröba, Andreas Paul (International Journal of Heat and Mass Transfer, 2024)
The present study examines the condensation heat transfer coefficient αcond of n-butane on the outside of different horizontal tubes and in corresponding tube bundles. Experiments were conducted with a smooth tube, finned tubes with various fin densities, fin heights and tube materials, and a high-performance condensation tube (HPT) at vapor temperatures of (40 and 78) °C and varying heat flux densities q̇. The influence of inundation on αcond was systematically investigated by varying the mass flow of liquid condensate at q̇ of (20 and 60) kW·m−2. Differences between the experimental results from this work and previous ones for propane on the same condensation tubes could be explained with the help of the thermophysical properties and, thus, the retention angle of the condensate in the channels between the fins and the condensate layer thickness. For single copper tubes, αcond increased with increasing fin densities from (19 to 48) fins per inch and was between 9 and 17 times larger than for the smooth tube. This enhancement factor even reached a value of about 24 for the HPT. These increases can be attributed in part to the increased surface area, but the strongest effect appears to be related to surface tension-driven drainage of the condensate. In addition to the experimental investigations, αcond of the finned condensation tubes was predicted using an analytical model for the condensation heat transfer on finned tubes. Here, excellent agreement with an average deviation from the experimental results of 6.6 % could be found. Studies of the inundation effect have shown that the expected decrease in αcond due to the additional condensate impinging on the tubes inside bundles and increasing the film thickness often holds, but is partially counteracted by other effects and depends on the tube geometr
Keywords: Finned tubes; n-Butane; Condensation heat transfer; Tube bundle; R600; Single tube